The Influence of Digital Payments and Financial Stressors on Consumptive Behavior of MNC University Students - Intan Aprilia; Dwiyanjana Santyo Nugroho (Eastasouth Institute, 2023)
This study aimed to determine the effect of digital payments and financial stressors on the consumptive behavior of MNC university students. This study uses quantitative research methods by distributing questionnaires to MNC university students with 62 samples from four majors. The result is that digital payments affect the student consumptive behavior of MNC University. The result is that digital payments and stressors simultan affect the student consumptive behavior of MNC University. But the financial stressors no affect the consumptive behavior of MNC University students. The weakness of this study is that it only uses one place as the object of research, so the findings cannot be generalized. Future research can increase the number of samples, not just focus on specific majors. It is recommended to increase the number of samples according to the majors at the University. Also, further research should add or replace other variables related to digital payments, financial stressors, and consumptive behavior.